2012
DOI: 10.1152/ajpendo.00539.2011
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial macronutrient transporter adaptations in the adult pregestational female intrauterine and postnatal growth-restricted offspring

Abstract: Associations between exponential childhood growth superimposed on low birth weight and adult onset cardiovascular disease with glucose intolerance/type 2 diabetes mellitus exist in epidemiological investigations. To determine the metabolic adaptations that guard against myocardial failure on subsequent exposure to hypoxia, we compared with controls (CON), the effect of intrauterine (IUGR), postnatal (PNGR), and intrauterine and postnatal (IPGR) calorie and growth restriction (n = 6/group) on myocardial macronu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…However at PN50 while the PNGR/IPGR males continued to demonstrate protection by elevated CSF ketones, this protection was absent in age-matched females. While we did not measure insulin or IGF-I at these early stages in this study, we have previously assessed them and noted insulin and IGF-I to be lower in PNGR and IPGR groups versus CON (Abbasi et al, 2011; Shin et al, 2012; Thamotharan et al, 2005). These hormonal changes are congenial for the use of alternate substrates to fuel brain energy metabolism.…”
Section: Discussionmentioning
confidence: 94%
“…However at PN50 while the PNGR/IPGR males continued to demonstrate protection by elevated CSF ketones, this protection was absent in age-matched females. While we did not measure insulin or IGF-I at these early stages in this study, we have previously assessed them and noted insulin and IGF-I to be lower in PNGR and IPGR groups versus CON (Abbasi et al, 2011; Shin et al, 2012; Thamotharan et al, 2005). These hormonal changes are congenial for the use of alternate substrates to fuel brain energy metabolism.…”
Section: Discussionmentioning
confidence: 94%
“…While this effect was also seen in non-IUGR rats, the effect was greatest in the IUGR diabetes-induced group (79). As measured by protein expression of glucose and fatty acid transporters, female IUGR offspring demonstrate resistance to insulin-induced translocation of several macronutrient transporters in the heart but overall increased expression of these proteins in the basal state (1). We have also previously demonstrated enhanced atherosclerotic patches in IUGR adult male mouse offspring associated with higher circulating cholesterol concentrations (7).…”
Section: Cardiovascular Sequelae Of Iugrmentioning
confidence: 74%
“…The pattern of decreased myocardial performance following Norwood palliation in males with higher SD ratios that mimics the pattern in SGA males parallels the findings of myocardial recovery in animal models of UPI and ischemia-reperfusion injury. [24][25][26] The long bypass and cross-clamp times needed to perform Norwood palliation represent a form of ischemiareperfusion injury. We found that males with UPI (as defined by the SD ratio) had impaired tolerance of this insult.…”
Section: Discussionmentioning
confidence: 99%